Interculturality in the normative framework of physical education in Colombia. Introitus to professional training - Hurtado Cerón, Arnulfo (2019)
This article presents the results of the research Interculturality and culture of indigenous peoples in the professional training process in Physical Education in Colombia; which aimed to recognize the presence or absence of diversity in the curricula of existing programs with active registration in the National Higher Education Information System of the country. It was approached methodologically from a dialogue between walking the spiral - Jijunan (understanding) and Kajijunan (interpretation) - proper of Colombian indigenous peoples and the content analysis technique; from which it aimed to infer and uncover what is latent in institutional documents of universities with courses in the field. There was little presence of these categories in the curricula of the current programs in Colombia.